Using a Narrative Approach to Understanding the Frontline Practices and Experiences of Aboriginal and Non-Aboriginal Child Protection Workers - Pooyak, Sherri; Gomez, Yvonne (First Peoples Child & Family Review, 2009)
This article reflects on the use of narrative analysis in understanding the experiences of two women, one Aboriginal and the other non-Aboriginal, each practicing in child welfare environments opposite of their cultural identities and worldviews.